Distal Aortic Remodeling after Type A Dissection Repair: An Ongoing Mirage - Kaushalendra Singh Rathore (Korean Society for Thoracic & Cardiovascular Surgery, 2021)
Remodeling is a commonly encountered term in the field of cardiothoracic surgery that is often used to describe various pathophysiological changes in the dimension, structure, and function of various cardiac chambers, including the aorta. Stanford type A or DeBakey type 1 aortic dissection (TAAD) is a perplexing pathologic condition that can present surgical teams with the need to navigate a maze of complex decision-making. Ascending or hemi-arch replacement leaves behind a significant amount of distal diseased aortic tissue, which might have a persistent false lumen or primary or secondary intimal tears (or communications between lumina), which can lead to dilatation of the aortic arch. Unfavorable aortic remodeling is a major cause of distal aortic deterioration after the index surgery. Cardiac surgeons are aware of post-surgical cardiac chamber remodeling, but the concept of distal aortic remodeling is still idealized. The contemporary literature from established aortic centers supports aggressive management of the residual aortic pathology during the index surgery, and with continuing technical advancements, endovascular stenting options are readily available for patients with TAAD or for complicated type B aortic dissection cases. This review discusses the pathophysiology and treatment options for favorable distal aortic remodeling, as well as its impact on mid- to long-term outcomes following TAAD repair.